Dental status in elderly with and without dementia living in a nursing home: a pilot study - Paulsen, Linda; Strindberg, Anette (Universitetet i Tromsø, 2011)
Several studies conducted in the latest decades in Norway have shown a remarkable decrease in the edentulous population. This along with the overall increase in the number of elderly presents tremendous challenges for the healthcare system in the future. Dementia is a condition that further complicates the oral health situation in the elderly population. In this pilot study we wanted to investigate whether there were any differences in the oral health status between the demented and the non-demented patients living in a nursing home in northern Norway. Looking at the dental records of 28 subjects we concluded that there were no differences of statistical significance related to dementia between the two groups. However, we could investigate other aspects such as geographical differences, age and gender, and comparing our results to former studies in Norway. Many of the dental records lacked information about health, medication and dental status. This not only makes it difficult to conduct a study, but could also compromise the ability of a dental practitioner to offer the correct treatment.